Who Needs Jobs? : Spreading Poverty or Increasing Welfare - Lemieux, Pierre; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
The goal should not be to create jobs, but to let people earn income in order to consume what they want.
Keywords: Labor market; Manpower policy